EVALUASI IMPLEMENTASI PENERAPAN PAJAK PROGRESIF KENDARAAN BERMOTOR DI KANTOR UNIT PENGELOLAAN PPENDAPATAN DAERAH (UPPD) SAMSAT SRAGEN - Sholekhah, Tasya Alvianita; Sugiyarti, Sri Riris; Suhita, Damayanti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Progressive motor vehicle tax is a tax imposed on private vehicles, both two-wheeledwithacapacity above 190 cc and four-wheeled, registered to the same owner and residence, aimedatreducing the number of vehicles. This research aims to evaluate the implementationofprogressive motor vehicle tax at the UPPD Samsat Sragen of ice. The type of this researchisqualitative and descriptive in nature. Data collection techniques were carried out throughobservation, interviews, and documentation. The data analysis techniques usedconsistofstages of data collection, data condensation, data presentation, and conclusionverification.This research uses William Nun Dun's theory which includes ef ectiveness, ef iciency,adequacy, fairness, responsiveness, and accuracy. The results of this study showthat theevaluation of the implementation of the progressive motor vehicle tax at the UPPDSamsatSragen of ice has been going well on indicators: adequacy, competent employee resources, andsuf icient facilities and infrastructure. Fairness, the implementation of progressive taxinSragen has been fair, and the community does not feel disadvantaged by the progressivetaxpolicy. The responsiveness of Samsat has provided a Complaints and Suggestions servicetogather feedback from the community regarding the progressive tax policy amongothers.However, it is still not optimal in terms of ef ectiveness; the implementation of the progressivetax at the Samsat Sragen of ice has not achieved the desired goal of addressing the problemofvehicle growth. Ef iciency, various ef orts have been made to reach the expectedgoals, butsocialization has not yet been ef icient. Accuracy in the collection of the progressive taxhasbeen carried out consistently without any violations or illegal collection practices. However, itis still not optimal in terms of tax collection and taxpayer compliance in payingtaxesandreporting name changes. Keywords: Evaluation, Motor Vehicle, Progressive Tax